Application of Co Ni intercalated vermiculite catalyst in pyrolysis of plastics. Issue 3 (April 2021) - Chen, Zicai; Wang, Yiqian; Sun, Zhipeng
Abstract: Currently, the amount of municipal solid wastes that are hardly degradable in nature keep increasing, of which the waste plastics account for a large proportion. There is no doubt that it will generate severer environmental issues. Therefore, we are expected to develop an efficient way to recycle the useful components in the mixed plastics to reduce the waste of energy and protect the environment. Thermal cracking, as a key technology for plastic recycling, can convert plastics into high value-added fuel products and broaden the sources of raw materials for ethylene, propylene and high value fuel production. For general catalysts, its catalytic activity is affected not only by the specific surface area and pore volume, but also by the acidity. In this paper, we try to construct an adjustable acidity catalyst by adopting vermiculite as the support, and sodium chloride, cetyltrimethylammonium bromide as modifier. That can provide exposed environment for the active sites in the bulk phase. At the same time, cobalt and nickel were used as intercalation to load on vermiculite. Ultimately, we obtained BET, XRD characterization data to determine the structure and properties of the catalyst, and analyzed the cracking products by GC quantitatively and qualitatively to build a reasonable structure-activity relationship.